2019
DOI: 10.1002/dmrr.3164
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces maternal weight gain in obese pregnant women: A systematic review and meta‐analysis of two randomized controlled trials

Abstract: Summary Obese pregnant women are likely to face several gestational and neonatal complications. Metformin is an effective oral antihyperglycaemic agent that is considered to be effective during pregnancy. The aim of our study was to evaluate the effect of metformin on obstetric and perinatal outcomes in obese pregnant women. Electronic databases were searched (MEDLINE, EMBASE, Web of Science, Scopus, http://ClinicalTrials.gov, OVID, and Cochrane Library). The selection criteria included only randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Previous meta-analyses estimated [69,72] that metformin reduced MWG by 1.35 to 1.49 kg, whereas the previous NMA [24] found no effect. Moreover, regarding exercise, the previous meta-analysis and NMA showed reductions of 1.14 and 0.96 kg, respectively [24,60].…”
Section: Discussionmentioning
confidence: 82%
“…Previous meta-analyses estimated [69,72] that metformin reduced MWG by 1.35 to 1.49 kg, whereas the previous NMA [24] found no effect. Moreover, regarding exercise, the previous meta-analysis and NMA showed reductions of 1.14 and 0.96 kg, respectively [24,60].…”
Section: Discussionmentioning
confidence: 82%
“…We concluded that this might be related to the weight-reducing effect of metformin [58]. However, several clinical research papers reported that metformin does not reduce the incidence of large gestational age newborns; it reduces the risk of neonatal intensive care unit admissions [58][59][60]. Related studies on metformin in the treatment of gestational diabetes and PCOS have shown that metformin can improve pregnancy outcomes [61][62][63][64].…”
Section: Discussionmentioning
confidence: 96%
“…Yet, these effects are not associated with an improvement in insulin sensitivity (Balani et al, 2017). Metformin does not reduce the incidence of large for gestational age newborns, nevertheless, it reduces the risk of neonatal intensive care unit admissions (Chiswick et al, 2015;Elmaraezy et al, 2017;D'Ambrosio et al, 2019;Dodd et al, 2019). Therefore, the beneficial effects of metformin on maternal and neonatal health when used in gestational obesity are still under debate and its prescription should be cautious.…”
Section: Gestational Obesitymentioning
confidence: 99%